Diploid porcine embryonic cell strains, cultures produced therefrom, and use of said cultures for production of vaccines - BORDT; DALE EMIL; THOMAS; PHILLIP CLAY (1978)
Diploid porcine embryonic cell strains, method of growing same from porcine embryonic tissue, culturing and subculturing said diploid cell strains, and preparing a virus vaccine (exemplary of the virus vaccine thus prepared is a porcine transmissible gastroenteritis virus vaccine) from said diploid cell strain cultures. A novel nutrient growth medium composition for culturing and subculturing by serial subcultivation is also disclosed.